Titanium-copper composite thin strip and multi-pass rolling composite method and device thereof

CN122999669APending Publication Date: 2026-10-30HAI AN & TAIYUAN UNIV OF TECH ADVANCED MFG & INTELLIGENT EQUIP IND RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611462958.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有制备技术如爆炸焊接、热压扩散及对称轧制存在显著缺陷:爆炸焊接易产生界面氧化和脆性相,且污染环境;热压扩散需高温长时间保温,能耗高且晶粒粗化严重;对称轧制因钛铜塑性差异大,界面结合强度低且易分层

Benefits of technology

[0027]1.先预制界面形貌,界面接触更充分:本发明不是直接将钛带和铜带叠合后进行一次复合轧制,而是先对钛带进行单带表面形貌预制轧制,使钛带一侧形成可控的形貌面,包括粗糙形貌、波纹形貌或阵列压印形貌,再将该形貌面作为钛铜复合界面。该形貌面在后续复合轧制中可压入铜层表面,提高界面真实接触面积和局部变形程度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999669A_ABST
    Figure CN122999669A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of layered metal composite thin strip preparation, and particularly relates to a titanium-copper composite thin strip and a multi-pass rolling composite method and device thereof. In order to solve the problems of insufficient interface bonding strength, poor titanium-copper deformation coordination, insufficient interface activation, unstable surface quality of finished products and difficulty in continuous preparation in the preparation process of traditional titanium-copper composite thin strip, the present application comprises: respectively pretreating titanium strips and copper strips; through pre-preparing a controllable morphology on the surface of the titanium strip, the titanium-copper laminated strip blank is obtained by using the morphology surface to contact and composite with the copper strip; the titanium-copper laminated strip blank is subjected to second-pass double-strip asymmetric composite rolling to form a titanium-copper primary composite thin strip; the titanium-copper primary composite thin strip is subjected to third-pass flat rolling to obtain a titanium-copper composite thin strip; if necessary, the titanium-copper composite thin strip is subjected to continuous short-time power-on treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of layered metal composite strip preparation technology, specifically relating to a titanium-copper composite strip and its multi-pass rolling composite method and apparatus. Background Technology

[0002] Titanium-copper composites possess the high strength and corrosion resistance of titanium and the excellent electrical conductivity of copper, making them widely used in electronic devices, aerospace, chemical engineering, and electrode materials for new energy batteries. Existing preparation techniques, such as explosive welding, hot-press diffusion, and symmetrical rolling, have significant drawbacks: explosive welding easily generates interfacial oxidation and brittle phases, and pollutes the environment; hot-press diffusion requires high-temperature, long-term holding, resulting in high energy consumption and severe grain coarsening; symmetrical rolling suffers from low interfacial bonding strength and delamination due to the large difference in plasticity between titanium and copper.

[0003] Therefore, a method is needed to solve the problems of insufficient interfacial bonding strength, poor coordination of titanium and copper deformation, insufficient interfacial activation, unstable surface quality of finished products, and difficulty in continuous preparation in the traditional titanium-copper composite strip preparation process. Summary of the Invention

[0004] To address the aforementioned problems, this invention provides a titanium-copper composite strip and its multi-pass rolling composite method and apparatus. By first pre-forming a controllable morphology surface on the titanium strip surface, and then using this morphology surface to contact and composite with the copper strip, the degree of fresh metal exposure at the interface and the degree of local plastic deformation are improved, enhancing the mechanical interlocking and metallurgical bonding of the titanium-copper interface. This is beneficial for improving the bonding strength, sheet shape quality, and continuous production efficiency of the composite strip.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] This invention provides a multi-pass rolling composite method for titanium-copper composite strips, comprising the following steps:

[0007] Step 1: Pre-treat the titanium strip and copper strip respectively;

[0008] Step 2: The pretreated titanium strip is fed into the first roll group for the first pass of single-strip surface morphology pre-rolling. The first roll group includes a first lower surface morphology roll located below the titanium strip and a first upper polishing roll located above the titanium strip, so that the lower side of the titanium strip in contact with the first lower surface morphology roll forms a morphology surface and the upper side in contact with the first upper polishing roll forms a smooth surface, thus obtaining a single-sided morphology titanium strip with a morphology surface on the lower side.

[0009] Step 3: Place the single-sided titanium strip on top of the pretreated copper strip, so that the morphological surface of the single-sided titanium strip faces and contacts the surface of the copper strip to be composited, to obtain a titanium-copper composite strip blank.

[0010] Step 4: The titanium-copper composite strip blank is fed into the second roll group for the second pass of double-strip asymmetric composite rolling. The second roll group includes a second upper surface morphology roll and a second lower polishing roll. The second upper surface morphology roll acts on the side of the titanium strip away from the copper strip, and the second lower polishing roll acts on the side of the copper strip away from the titanium strip. After rolling, a titanium-copper initial composite thin strip is formed.

[0011] Step 5: The titanium-copper initial composite strip is fed into the third roll group for the third pass of leveling rolling, so that the upper and lower outer surfaces of the titanium-copper initial composite strip are flattened to obtain the titanium-copper composite strip. The third roll group includes two flat rolls.

[0012] Furthermore, the first lower surface morphology roller and the second upper surface morphology roller are preferably textured rollers. The textured roller can form random, non-periodic, and uniformly distributed micro-peaks and micro-pits on the roller surface through sandblasting, electrical discharge machining, or laser texturing. These micro-peaks and micro-pits together constitute a rough working surface. The first lower surface morphology roller is used to imprint a random rough morphology on the underside of the titanium strip, ensuring that this rough morphology directly faces the copper strip during subsequent lamination. The second upper surface morphology roller acts on the titanium side during titanium-copper composite rolling, increasing friction and local shearing on the titanium side, further pressing the pre-formed rough morphology into the copper layer, increasing the actual contact area at the interface, and facilitating oxide film rupture and fresh metal contact. The surface roughness Ra of the textured roller is 2.0–6.0 μm, and the surface roughness Ra of the first upper polishing roller and the second lower polishing roller is 0.03–0.1 μm.

[0013] In addition to the preferred texturing roller, the surface morphology roller can also be a corrugated roller or an array of raised rollers, and the selection can be made according to the target interface morphology. The working surface of the corrugated roller has continuous peaks and troughs extending along the axial direction of the roll and periodically distributed along the circumference of the roll, wherein the corrugation height is denoted as h. w The center-to-center distance between adjacent wave crests is denoted as p. w The radius of the crest fillet is denoted as r. c The radius of the trough fillet is denoted as r. v The corrugation height h w The distance between the centers of the adjacent peaks is 5–50 μm. w The radius of the wave crest radius r is 50–500 μm. c and the radius of the trough rounded corner r v All are 20–250 μm. The working surface of the array of raised rollers has multiple raised protrusions regularly distributed along the axial and circumferential directions of the roller. The raised protrusions can be frustums of cylinders, frustums of cones, hemispheres, or pyramids. The diameter or equivalent lateral dimension of the bottom of the raised protrusion is denoted as d, and the height of the raised protrusion is denoted as h. t The axial center distance between adjacent protrusions is denoted as p. x The circumferential center distance is denoted as p. yThe diameter or equivalent lateral dimension d of the bottom of the protrusion is 50-300 μm, and the height h of the protrusion is... t The diameter is 5–50 μm, and the axial center distance is p. x and circumferential center distance p y Both are 100–500 μm. The first lower surface morphology roller and the second upper surface morphology roller can use the same or different roller surface morphology types.

[0014] Furthermore, the titanium strip can be made of industrial pure titanium or titanium alloy, including but not limited to TA1, TA2, TA3, TC4, etc.; the copper strip can be made of pure copper or copper alloy, including but not limited to T1, T2, T3 and other copper alloys with good plastic deformation ability.

[0015] Furthermore, the pretreatment of titanium strip and copper strip in step 1 is specifically as follows: the titanium strip with a thickness of 0.1 to 0.2 mm is pickled and polished to remove the surface oxide film and activate the surface to be laminated; the copper strip with a thickness of 0.1 to 0.3 mm is polished or ground to obtain a clean surface to be laminated.

[0016] Furthermore, in step 2, the reduction rate of the first pass single-strip surface morphology pre-rolling is 3% to 20%; the morphology surface is a rough morphology, a corrugated morphology, or an array imprinted morphology; the surface roughness Ra of the morphology surface is 1.0 to 4.5 μm, or the morphology height is 3 to 40 μm.

[0017] Furthermore, the reduction rate of the second pass of the double-strip asymmetric composite rolling in step 4 is 10% to 45%.

[0018] Furthermore, in step 5, the reduction rate of the third leveling rolling is 3% to 15%, and the surface roughness Ra of the upper and lower outer surfaces of the titanium-copper composite strip is not greater than 0.5 μm.

[0019] Further, after step 2 and before step 3, surface morphology detection sensors located above and below the single-sided morphology titanium strip are used for detection. The surface morphology detection sensor located above is used to detect the surface condition of the upper polished surface of the titanium strip, and the surface morphology detection sensor located below is used to detect the surface roughness or contour parameters of the lower morphology surface of the titanium strip. When the detection result of the lower morphology surface does not meet the preset range, feeding is stopped and the first lower surface morphology roller is adjusted or replaced. When the detection result of the upper polished surface does not meet the preset range, feeding is stopped and the first upper polishing roller is checked, adjusted or replaced.

[0020] Furthermore, the method also includes an energizing process, in which the titanium-copper composite strip is fed into an online energizing device for continuous short-term energizing. The online energizing device is located between the third roll group and the winding mechanism. The online energizing device includes at least two electrodes spaced apart along the strip's running direction and a temperature detection device. The electrodes are in conductive contact with the titanium-copper composite strip and connected to an adjustable current power supply, inputting current to the titanium-copper composite strip through adjacent electrodes. The temperature detection device is located in the energizing area between adjacent electrodes to detect the strip temperature in real time within the energizing area and adjust the current input according to the detected temperature, controlling the energizing temperature between 500 and 900 °C, with an effective energizing time of 5 to 15 seconds. The energizing process is performed under a protective atmosphere, vacuum environment, or inert gas protection. By adjusting the current input and the effective energizing time, continuous short-term energizing of the titanium-copper composite strip is achieved to reduce residual stress and improve the interfacial bonding state.

[0021] The present invention also provides a titanium-copper composite strip, which is prepared by the above-mentioned multi-pass rolling composite method for titanium-copper composite strip.

[0022] The present invention also provides a multi-pass rolling composite device for titanium-copper composite strip, which is applicable to the multi-pass rolling composite method for titanium-copper composite strip, including a titanium strip uncoiling mechanism, a first roll group, a second roll group, a third roll group and a winding mechanism arranged sequentially along the production line;

[0023] A copper strip uncoiling mechanism is provided below the titanium strip uncoiling mechanism. Guide mechanisms are provided between the titanium strip uncoiling mechanism and the first roll group, and between the copper strip uncoiling mechanism and the second roll group. The first roll group includes a first lower surface morphology roll located below the titanium strip and a first upper polishing roll located above the titanium strip. The second roll group includes a second upper surface morphology roll and a second lower polishing roll. The third roll group includes two flat rolls.

[0024] Furthermore, it also includes an online energizing device, disposed between the third roll group and the winding mechanism. The online energizing device includes at least two electrodes spaced apart along the strip's running direction and a temperature detection device. The electrodes are in conductive contact with the titanium-copper composite strip and connected to an adjustable current power supply for inputting current into the titanium-copper composite strip between adjacent electrodes. The temperature detection device is disposed in the energized area between adjacent electrodes for detecting the temperature of the titanium-copper composite strip within the energized area and outputting the temperature detection result. The current input of the adjustable current power supply is adjusted according to the temperature detection result.

[0025] Furthermore, surface morphology detection sensors are respectively installed between the first and second roll groups, above and below the single-sided morphology titanium strip. The upper surface morphology detection sensor is used to detect the surface condition of the upper polished surface of the single-sided morphology titanium strip, and the lower surface morphology detection sensor is used to detect the surface roughness or contour parameters of the lower morphology surface. When the detection results of the upper polished surface and the lower morphology surface both meet the corresponding preset range, the strip continues to run. When the detection result of the lower morphology surface does not meet the corresponding preset range, the feeding stops, and the first lower surface morphology roll is adjusted or replaced. When the detection result of the upper polished surface does not meet the corresponding preset range, the feeding stops, and the first upper polishing roll is checked, adjusted or replaced.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1. Pre-fabrication of interface morphology for more thorough interface contact: This invention does not directly stack titanium and copper strips and then perform a single composite rolling process. Instead, it first pre-fabricates the surface morphology of the titanium strip using single-strip rolling, creating a controllable morphology surface on one side of the titanium strip, including rough morphology, corrugated morphology, or array imprinted morphology. This morphology surface then serves as the titanium-copper composite interface. This morphology surface can be pressed into the copper layer surface during subsequent composite rolling, increasing the actual contact area and the degree of local deformation.

[0028] 2. It is beneficial to enhance mechanical interlocking: the micro-protrusions, ripples or array imprints on the surface of the titanium strip interlock with the copper layer during the second-pass composite rolling process, so that the titanium-copper interface changes from a relatively flat interface to a composite interface with undulating features, which is beneficial to improve interface stability and anti-delamination ability.

[0029] 3. Promote fresh metal exposure and subsequent metallurgical bonding: In the second pass of composite rolling, the titanium strip morphology can exert local extrusion, shearing and plowing effects on the copper strip surface, which is conducive to breaking the interface oxide film, promoting the contact of fresh titanium and copper metals, and creating conditions for subsequent metallurgical bonding and diffusion bonding.

[0030] 4. Increasing the participation of titanium-side deformation and reducing the reduction rate required for composite processing: The second-pass composite rolling uses an upper surface morphology roll and a lower polishing roll configuration. The upper surface morphology roll acts on the titanium side, which can increase titanium-side friction and local shear deformation, promoting the participation of the more difficult-to-deform titanium layer in plastic flow. The results in Table 1 show that the texturing roll-polishing roll group can achieve titanium-copper strip composite at a reduction rate of 10%, while the double polishing roll group only achieves composite when the reduction rate reaches 30%. This indicates that the present invention is beneficial to reducing the reduction rate required to achieve composite processing, reducing the risk of excessive strip thinning, uncontrolled layer thickness ratio, and deterioration of strip shape. The lower polishing roll acts on the copper side, which can reduce additional damage to the outer surface of the copper layer, thereby taking into account interface formation, thickness control, and outer surface quality.

[0031] 5. The third leveling rolling takes into account both interface morphology and surface quality: The final double-flat roll leveling rolling can further flatten the undulations on the outer surface formed after the second composite rolling, improve the surface quality and shape of the composite strip, and at the same time retain the undulation bonding characteristics at the interface.

[0032] 6. Online inspection improves process stability: By setting upper and lower surface morphology detection sensors after the first pass of single strip surface morphology pre-rolling, the morphology surface and the finished surface can be inspected before entering the composite rolling, preventing titanium strips with unqualified morphology from continuing to enter subsequent processes.

[0033] 7. Simple process, suitable for continuous production of thin strips: The multi-pass rolling composite device used in this invention has a clear structure and does not require explosive welding conditions or long-term high-temperature diffusion treatment; by integrating surface morphology pre-fabrication, online detection, double strip composite rolling, leveling rolling and online short-time energization treatment on a continuous production line, the composite thin strip can be rapidly processed by adjusting the current input and energization time, thereby improving the continuous production efficiency and product consistency of titanium-copper composite thin strips. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the structure of the multi-pass rolling composite device of the present invention;

[0035] Figure 2 This is a process flow diagram of the multi-pass rolling composite method of the present invention;

[0036] Figure 3 The images show the surface morphology of the lower side of the titanium strip, where (a) is the titanium strip after pretreatment and before the first pass surface morphology pre-rolling, and (b) is the titanium strip after the first pass surface morphology pre-rolling.

[0037] Figure 4 The SEM images show the interface morphology of titanium-copper composite strips, where (a) is the result of asymmetric multi-pass rolling and (b) is the result of double polishing roll rolling.

[0038] Figure 5 The images show a comparison of the texturing roller and the polishing roller, where (a) is the texturing roller and (b) is the polishing roller.

[0039] Figure 6 Here are schematic diagrams of other surface morphology rollers, where (a) is a schematic diagram of the overall structure of the corrugated roller and (b) is a schematic diagram of the overall structure of the array protrusion roller.

[0040] In the figure, 1 is the titanium strip uncoiling mechanism, 2 is the copper strip uncoiling mechanism, 3 is the first roll group, 31 is the first lower surface morphology roll, 32 is the first upper polishing roll, 4 is the second roll group, 41 is the second upper surface morphology roll, 42 is the second lower polishing roll, 5 is the third roll group, 51 is the flat roll, 6 is the online power-on processing device, 61 is the electrode, 62 is the temperature detection device, 7 is the winding mechanism, 8 is the guiding mechanism, and 9 is the surface morphology detection sensor. Detailed Implementation

[0041] To further illustrate the technical solution of the present invention, the present invention will be further described below through embodiments.

[0042] Example 1

[0043] like Figure 1 As shown, a multi-pass rolling composite device for titanium-copper composite strip in this embodiment includes a titanium strip uncoiling mechanism 1, a first roll group 3, a second roll group 4, a third roll group 5, an online power-on processing device 6, and a winding mechanism 7 arranged sequentially along the production line.

[0044] A copper strip uncoiling mechanism 2 is provided below the titanium strip uncoiling mechanism 1. Guide mechanisms 8 are provided between the titanium strip uncoiling mechanism 1 and the first roll group 3, and between the copper strip uncoiling mechanism 2 and the second roll group 4. The guide mechanisms 8 guide the strip, ensuring that the single-sided titanium strip formed after rolling by the first roll group 3 maintains its morphological surface facing down and directly runs above the copper strip to overlap with the surface to be laminated, without needing to flip it. The first roll group 3 includes a first lower surface morphological roll 31 located below the titanium strip and a first upper polishing roll 32 located above the titanium strip. The second roll group 4 includes a second upper surface morphological roll 41 and a second lower polishing roll 42. The third roll group 5 includes two flat rolls 51.

[0045] The online energizing device 6 is located between the third roll group 5 and the winding mechanism 7, and includes at least two electrodes 61 spaced apart along the strip running direction and a temperature detection device 62. Each electrode 61 is in conductive contact with the titanium-copper composite strip and connected to an adjustable current power supply, allowing current to flow through the titanium-copper composite strip between adjacent electrodes 61. The temperature detection device 62 is located in the energized area between adjacent electrodes 61 and is used to detect the temperature of the titanium-copper composite strip in the energized area in real time, and adjust the current input of the adjustable current power supply according to the temperature detection result.

[0046] Between the first roll group 3 and the second roll group 4, surface topography detection sensors 9 are respectively installed above and below the single-sided titanium strip. The surface topography detection sensor 9 located above is used to detect the surface condition of the smooth surface on the upper side of the titanium strip, and the surface topography detection sensor 9 located below is used to detect the surface roughness or contour parameters of the bottom surface of the titanium strip.

[0047] When the detection results of the upper surface finishing and the lower surface morphology both meet the corresponding preset range, the strip continues to enter the second roll group 4; when the detection result of the lower surface morphology does not meet the corresponding preset range, the feeding stops and the first lower surface morphology roll 31 is adjusted or replaced; when the detection result of the upper surface finishing does not meet the corresponding preset range, the feeding stops and the first upper polishing roll 32 is inspected, adjusted or replaced.

[0048] Example 2

[0049] like Figure 2 As shown, this embodiment describes a multi-pass rolling composite method for titanium-copper composite strips, employing the multi-pass rolling composite apparatus described in Embodiment 1. This embodiment illustrates the specific process of first performing single-strip surface morphology pre-rolling, followed by double-strip asymmetric composite rolling, and compares it with the double-polished-roll rolling method, including the following steps:

[0050] Step 1, Material Pretreatment:

[0051] TA1 titanium strip with a thickness of 0.10 mm and T2 copper strip with a thickness of 0.10 mm are selected as composite raw materials. This embodiment uses TA1 titanium strip and T2 copper strip as examples for illustration. The material grades mentioned do not constitute a limitation on the scope of application of the materials in this invention. Other industrial pure titanium, titanium alloys, pure copper, or copper alloys can also be used, provided that the corresponding thickness, plastic deformation, and composite rolling requirements are met. The titanium strip is pickled and mechanically polished to remove the surface oxide film and activate the surface to be composited. The surface to be composited on the copper strip is mechanically polished to remove surface contaminants and obtain a clean surface. After pretreatment, the titanium strip and copper strip are cleaned and dried separately, taking care to avoid recontamination of the surfaces to be composited.

[0052] Step 2, First pass single-strip surface morphology pre-rolling:

[0053] The pretreated titanium strip is fed separately into the first roll group for the first pass of single-strip surface morphology pre-rolling. The first roll group includes a first lower surface morphology roll 31 located below the titanium strip and a first upper polishing roll 32 located above the titanium strip. The first lower surface morphology roll 31 is a textured roll obtained through sandblasting, with its surface exhibiting random, non-periodic distribution of micro-peaks and micro-pits, and a surface roughness Ra of 3.0 μm. The first upper polishing roll 32 has a surface roughness Ra of 0.03–0.10 μm. The textured roll is used to imprint a random rough morphology on the underside of the titanium strip, while the first upper polishing roll 32 is used to maintain a relatively smooth upper surface of the titanium strip. A physical comparison of the textured roll and the polishing roll is provided. Figure 5 As shown.

[0054] The reduction rate of the first pass single-strip surface morphology pre-rolling is 10%, which forms a rough morphology surface on the lower side of the titanium strip in contact with the first lower surface morphology roll 31, and a smooth surface on the upper side in contact with the first upper polishing roll 32, resulting in a single-sided morphology titanium strip with a rough morphology surface on the lower side. Figure 3 As shown, compared with the titanium strip before the first rolling pass, the lower surface of the titanium strip forms a distinct undulating morphology after the first rolling pass surface morphology pre-forming.

[0055] After the first pass of single-strip surface morphology pre-rolling, surface morphology detection sensors 9, located above and below the titanium strip, are used for detection. The upper sensor 9 detects the surface condition of the upper polished surface of the titanium strip, while the lower sensor 9 detects the surface roughness or contour parameters of the lower morphology surface. If the detection result of the lower morphology surface does not meet the corresponding preset range, feeding stops, and the first lower surface morphology roller 31 is adjusted or replaced. If the detection result of the upper polished surface does not meet the corresponding preset range, feeding stops, and the first upper polishing roller 32 is inspected, adjusted, or replaced. In this embodiment, the strip continues to run when the detection results of both the upper polished surface and the lower morphology surface meet the corresponding preset range.

[0056] Step 3, stacking and blanking:

[0057] The titanium strip with a shaped surface on its lower side is guided above the pretreated copper strip, so that the lower shaped surface of the titanium strip faces downward and directly contacts the upper surface of the copper strip to be laminated, thus obtaining a titanium-copper laminated strip blank. Since the first lower surface shaped roller 31 is located below the titanium strip, the titanium strip can be laminated without flipping after leaving the first roll group 3.

[0058] Step 4, Second pass of double-strip asymmetric composite rolling:

[0059] The titanium-copper composite strip is fed into the second roll group for a second pass of asymmetric composite rolling. The second roll group includes a second upper surface morphology roll and a second lower polishing roll. The second upper surface morphology roll is a roughened roll obtained by sandblasting, with randomly distributed micro-peaks and micro-pits on its surface, and a surface roughness Ra of 3.0 μm. The surface roughness Ra of the second lower polishing roll is 0.03–0.1 μm. During composite rolling, the second upper surface morphology roll acts on the titanium side to increase friction and interfacial shearing on the titanium side and promote the indentation of the pre-roughened titanium strip morphology into the copper layer. The second lower polishing roll acts on the copper side to reduce additional damage to the outer surface of the copper layer.

[0060] In the second pass of double-strip asymmetric composite rolling, the second upper surface morphology roll acts on the side of the titanium strip away from the copper strip, and the second lower polishing roll acts on the side of the copper strip away from the titanium strip; the reduction rate of the second pass of double-strip asymmetric composite rolling is 35%, and a titanium-copper primary composite thin strip is formed after rolling.

[0061] Step 5, third leveling and rolling:

[0062] The titanium-copper initial composite strip is fed into the third roll group for a third pass of leveling rolling. The third roll group includes two flat rolls. The reduction rate of the third pass of leveling rolling is 5%, which flattens the upper and lower outer surfaces of the titanium-copper initial composite strip to obtain a titanium-copper composite strip. The surface roughness Ra of the upper and lower outer surfaces of the titanium-copper composite strip is not greater than 0.5 μm.

[0063] Other optional settings for surface topography rolls and rolling parameters:

[0064] Based on the above embodiments, the roll surface morphology type, roll surface morphology parameters, and corresponding rolling parameters of the first lower surface morphology roll 31 and the second upper surface morphology roll 41 can be adjusted according to the titanium strip thickness, target interface morphology, and rolling equipment capacity. Except for the roll surface morphology and rolling parameters described below, the material pretreatment method, the stacking billet preparation method, the third pass leveling rolling method, and the coiling method of the titanium strip and copper strip are all the same as the steps described in this embodiment.

[0065] In one optional configuration, both the first lower surface morphology roll 31 and the second upper surface morphology roll 41 are textured rolls obtained through sandblasting, and the surface roughness Ra of the textured rolls is 2.0 μm. The reduction rate of the first pass single-strip surface morphology pre-rolling is 5%, which forms a randomly distributed rough morphology on the side of the titanium strip that contacts the first lower surface morphology roll 31; the reduction rate of the second pass double-strip asymmetric composite rolling is 30%; and the reduction rate of the third pass leveling rolling is 3% to 15%.

[0066] In another optional configuration, both the first lower surface morphology roll 31 and the second upper surface morphology roll 41 are textured rolls obtained by sandblasting, and the surface roughness Ra of the textured rolls is 5.0 μm. The reduction rate of the first pass single-strip surface morphology pre-rolling is 15%, the reduction rate of the second pass double-strip asymmetric composite rolling is 40%, and the reduction rate of the third pass leveling rolling is 3% to 15%.

[0067] In another optional configuration, both the first lower surface morphology roller 31 and the second upper surface morphology roller 41 are corrugated rollers. For example... Figure 6 As shown in (a), the working surface of the corrugated roll has continuous peaks and troughs extending along the roll axial direction and periodically distributed along the roll circumference. The corrugation height h w The value is 20 μm, and the center distance between adjacent peaks is p. w 200 μm, crest radius r c and the radius of the trough rounded corner r vAll are 100 μm. The reduction rate of the first pass single-strip surface morphology pre-rolling is 10%, so that one side of the titanium strip forms a corrugated morphology corresponding to the corrugated roll surface; the reduction rate of the second pass double-strip asymmetric composite rolling is 35%; the reduction rate of the third pass leveling rolling is 3% to 15%.

[0068] In another optional configuration, both the first lower surface morphology roller 31 and the second upper surface morphology roller 41 are arrayed raised rollers. For example... Figure 6 As shown in (b), the working surface of the array of raised rollers has multiple cylindrical frustum-shaped protrusions arranged regularly along the axial and circumferential directions of the roller. The bottom diameter d of each protrusion is 100 μm, and the height h of each protrusion is... t The axial center distance p between adjacent protrusions is 20 μm. x and circumferential center distance p y All are 200 μm. The reduction rate of the first pass single-strip surface morphology pre-rolling is 10%, so that one side of the titanium strip forms an array imprint morphology corresponding to the array of raised roll surfaces; the reduction rate of the second pass double-strip asymmetric composite rolling is 35%; the reduction rate of the third pass leveling rolling is 3% to 15%.

[0069] In other optional configurations, the first lower surface morphology roll 31 and the second upper surface morphology roll 41 can be of the same type or different types. The first lower surface morphology roll 31 is used to pre-form corresponding rough morphology, corrugated morphology, or array imprinted morphology on the titanium strip to be composited surface; the second upper surface morphology roll 41 is used to increase titanium side friction and local shearing action during the second pass of double-strip asymmetric composite rolling, and to promote contact between the pre-formed titanium strip morphology and the copper strip to be composited surface.

[0070] The above optional settings are used to describe how the roll surface morphology type, roll surface morphology parameters, and first and second pass rolling parameters can be combined and adjusted according to the strip specifications, target interface morphology, and rolling equipment capabilities. In specific applications, the titanium strip morphology parameters formed after the first pass rolling, the reduction rate of each pass, and the final surface quality of the composite strip should be within the corresponding ranges described in this specification.

[0071] Comparative Example 1

[0072] This comparative example uses a double-polished-roll rolling method to prepare titanium-copper composite strips. Compared with Example 2, both the first pass of single-strip rolling and the second pass of double-strip composite rolling use upper and lower double polished rolls, without pre-forming a single-sided rough morphology on the titanium strip surface; except for the roll surface configuration, the raw material specifications, material pretreatment methods, lamination methods, rolling speeds, third pass leveling rolling conditions, and composite state determination methods are consistent in both sets of experiments.

[0073] To evaluate the effect of surface morphology prefabrication and the configuration of texturing rolls and polishing rolls on the low reduction rate composite capability, the reduction rate of the second pass composite rolling was set to 10%, 20%, 30%, and 40%, respectively. The texturing roll-polishing roll group in Example 2 and the double polishing roll group in Comparative Example 1 were used for composite rolling, and it was observed whether each group of samples achieved stable composite. At the same time, the corresponding samples were selected for cross-sectional SEM observation.

[0074] Table 1. Titanium-copper strip composite under different reduction rates with two roll combinations.

[0075] 10% Y N 20% Y N 30% Y Y 40% Y Y

[0076] Note: Y indicates that the sample achieved composite, and N indicates that the sample did not achieve composite.

[0077] As shown in Table 1, within the reduction rate range of 10% to 40%, the texturing roll-polishing roll group can achieve titanium-copper strip composite at reduction rates of 10%, 20%, 30%, and 40%. The dual polishing roll group did not achieve composite at reduction rates of 10% and 20%, only achieving composite at reduction rates of 30% and above. Therefore, under the experimental conditions, the texturing roll-polishing roll configuration significantly reduces the reduction rate required for titanium-copper strip composite: the texturing roll-polishing roll group can achieve composite at a reduction rate of 10%, while under the tested discrete reduction rate conditions, composite was first observed with the dual polishing roll group at a reduction rate of 30%, with the critical reduction rate required for composite being greater than 20% and not higher than 30%. These results demonstrate that the present invention, by pre-fabricating the surface morphology of the titanium strip to be composited and employing a texturing roll-polishing roll configuration during the composite rolling process, is beneficial for enhancing local interface contact, shear deformation, and mechanical interlocking, enabling titanium-copper strip composite to be achieved with a relatively small overall thickness reduction. Therefore, the present invention can reduce the risks of excessive strip thinning, uncontrolled layer thickness ratio and deterioration of strip shape caused by using a large reduction rate to obtain interfacial composite, expand the available process window of titanium-copper ultrathin composite strip, and improve the controllability and stability of continuous composite rolling process.

[0078] like Figure 4 As shown, both rolling methods resulted in relatively continuous titanium-copper composite strips with no obvious through gaps or macroscopic interface delamination. Specifically, the interface of the sample obtained from the texturing roll-polishing roll combination exhibited gentle undulations, while the interface of the sample rolled by the double polishing rolls was relatively straight, indicating that different roll configurations can control the morphological characteristics of the titanium-copper composite interface. Combined with the results in Table 1, it can be seen that the pre-fabricated surface morphology and the localized friction, shearing, and plastic deformation introduced by the texturing rolls are beneficial for interface bonding and mechanical interlocking.

[0079] Example 3

[0080] The difference between this embodiment and embodiment 2 is that a continuous short-time energization process is added after the third pass leveling rolling. The other material pretreatment, surface morphology pre-rolling, second pass double-strip asymmetric composite rolling and third pass leveling rolling conditions are the same as in embodiment 2.

[0081] The titanium-copper composite strips prepared in Example 2 were divided into four groups. One group was not subjected to electrification treatment and served as a control group in the rolled state. The other three groups were treated with different electrification regimes. During the electrification process, the titanium-copper composite strips were in conductive contact with the electrodes 61 in the online electrification treatment device 6. An adjustable current power supply was used to input current to the titanium-copper composite strips through the electrodes 61. The temperature of the titanium-copper composite strips in the electrified area was detected in real time using a temperature detection device 62. The current input was adjusted according to the detected temperature so that the strips in each group reached the corresponding electrification treatment temperature. The electrification treatment temperature of the first electrified group was 500 ℃, and the electrification time was 5 s; the electrification treatment temperature of the second electrified group was 700 ℃, and the electrification time was 10 s; the electrification treatment temperature of the third electrified group was 900 ℃, and the electrification time was 15 s. All groups were electrified under the same protective atmosphere conditions, and after the electrification treatment, they were cooled to room temperature using the same cooling method.

[0082] To evaluate the effect of electrostatic treatment on the interfacial bonding performance of titanium-copper composite strips, peel tests were conducted on rolled samples and samples treated with different electrostatic regimes. The same sample size and test conditions were used for each group of samples, and the test results are shown in Table 2.

[0083] Table 2. Peel strength of titanium-copper composite strips under different electrical conditions

[0084] as-rolled — — 0.3±0.1 first energizing set 500 5 1.0±0.2 second energizing set 700 10 9.1±0.5 third energizing set 900 15 6.0±0.5

[0085] Table 2 shows that the peel strength of the rolled titanium-copper composite strip is 0.3 N / mm. After energizing at 500 °C for 5 s, the peel strength increases to 1.0 N / mm; after energizing at 700 °C for 10 s, the peel strength increases to 9.1 N / mm; and after energizing at 900 °C for 15 s, the peel strength is 6.0 N / mm. Among the three energizing conditions tested in this embodiment, the sample with the highest peel strength was obtained under the condition of 700 °C for 10 s. The above results indicate that the interfacial bonding performance of the titanium-copper composite strip can be controlled by adjusting the current input and controlling the energizing time; under the conditions of this embodiment, a suitable energizing treatment regime can improve the peel strength of the composite strip.

[0086] The foregoing has shown and described the main features and advantages of the present invention. For those skilled in the art, the present invention is not limited to the details of the exemplary embodiments described above, and may be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, all embodiments should be understood as exemplary rather than restrictive, and the scope of protection of the present invention is determined by the appended claims. Variations falling within the meaning and scope of equivalents of the claims should be included within the scope of protection of the present invention.

Claims

1. A multi-pass rolling composite method for titanium-copper composite strips, characterized in that, Includes the following steps: Step 1: Pre-treat the titanium strip and copper strip respectively. The thickness of the titanium strip is 0.1-0.2 mm and the thickness of the copper strip is 0.1-0.3 mm. Step 2: The pretreated titanium strip is fed into the first roll group for the first pass of single-strip surface morphology pre-rolling. The first roll group includes a first lower surface morphology roll located below the titanium strip and a first upper polishing roll located above the titanium strip, so that the lower side of the titanium strip in contact with the first lower surface morphology roll forms a morphology surface and the upper side in contact with the first upper polishing roll forms a smooth surface, thus obtaining a single-sided morphology titanium strip with a morphology surface on the lower side. Step 3: Guide the single-sided titanium strip to the top of the pretreated copper strip, so that the lower morphological surface of the single-sided titanium strip faces and contacts the upper surface of the copper strip to be composited, to obtain a titanium-copper composite strip blank. Step 4: The titanium-copper composite strip blank is fed into the second roll group for the second pass of double-strip asymmetric composite rolling. The second roll group includes a second upper surface morphology roll and a second lower polishing roll. The second upper surface morphology roll acts on the side of the titanium strip away from the copper strip, and the second lower polishing roll acts on the side of the copper strip away from the titanium strip. After rolling, a titanium-copper initial composite thin strip is formed. Step 5: The titanium-copper initial composite strip is fed into the third roll group for the third pass of leveling rolling, so that the upper and lower outer surfaces of the titanium-copper initial composite strip are flattened to obtain the titanium-copper composite strip. The third roll group includes two flat rolls.

2. The multi-pass rolling composite method for titanium-copper composite strip according to claim 1, characterized in that, The first lower surface morphology roller and the second upper surface morphology roller are each independently selected from one of the texturing roller, corrugated roller or array protrusion roller, and the roller surface morphology types of the two are the same or different; The surface roughness Ra of the first upper polishing roller and the second lower polishing roller is 0.03 to 0.10 μm; The surface of the texturing roller has random, non-periodic distribution of micro-peaks and micro-pits, and the surface roughness Ra of the texturing roller is 2.0 to 6.0 μm. The working surface of the corrugated roll has continuous peaks and troughs extending along the roll axial direction and periodically distributed along the roll circumference. The height difference between the peaks and adjacent troughs is the corrugation height h. w The corrugation height h w The wavelength range is 5–50 μm, and the center-to-center distance between adjacent peaks is p. w The wavelength ranges from 50 to 500 μm, and the radius of curvature of the wave crest is r. c and the radius of the trough rounded corner r v All are 20–250 μm; The working surface of the array of raised rollers is provided with multiple raised protrusions regularly distributed along the axial and circumferential directions of the roller. Each protrusion is at least one of a truncated cylindrical, truncated conical, hemispherical, or pyramidal shape. The bottom diameter d1 of the truncated cylindrical, truncated conical, or hemispherical protrusion, or the equivalent lateral dimension d2 of the pyramidal protrusion, is 50–300 μm, and the protrusion height h is [not specified]. t The axial center distance p between adjacent protrusions is 5–50 μm. x and circumferential center distance p y All range from 100 to 500 μm.

3. The multi-pass rolling composite method for titanium-copper composite strip according to claim 1, characterized in that, In step 1, the titanium strip is pickled and polished to remove the surface oxide film and activate the surface to be laminated; the copper strip is polished or ground to obtain a clean surface to be laminated.

4. The multi-pass rolling composite method for titanium-copper composite strip according to claim 1, characterized in that, After step 2 and before step 3, surface morphology detection sensors located above and below the single-sided titanium strip are used for detection. The upper surface morphology detection sensor is used to detect the surface condition of the upper polished surface of the titanium strip, and the lower surface morphology detection sensor is used to detect the surface roughness or contour parameters of the lower morphology surface of the titanium strip. When the detection result of the lower morphology surface does not meet the preset range, feeding is stopped and the first lower surface morphology roller is adjusted or replaced. When the detection result of the upper polished surface does not meet the preset range, feeding is stopped and the first upper polishing roller is checked, adjusted or replaced.

5. The multi-pass rolling composite method for titanium-copper composite strip according to claim 1, characterized in that, In step 2, the reduction rate of the first pass single-strip surface morphology pre-rolling is 3% to 20%, and the morphology surface is a rough morphology, a corrugated morphology, or an array imprinted morphology. The surface roughness Ra of the morphology surface is 1.0 to 4.5 μm, or the morphology height is 3 to 40 μm. In step 4, the reduction rate of the second pass of double-strip asymmetric composite rolling is 10% to 45%. In step 5, the reduction rate of the third leveling rolling is 3% to 15%, and the surface roughness Ra of the upper and lower outer surfaces of the titanium-copper composite strip is not greater than 0.5 μm.

6. The multi-pass rolling composite method for titanium-copper composite strip according to claim 1, characterized in that, The method further includes an energizing process, in which the titanium-copper composite strip is fed into an online energizing device located between the third roll group and the winding mechanism for continuous short-term energizing. The online energizing device includes at least two electrodes spaced apart along the strip's running direction and a temperature detection device for detecting the strip's temperature. The electrodes are in conductive contact with the titanium-copper composite strip and connected to an adjustable current power supply for inputting current into the titanium-copper composite strip. The temperature detection device is located in the energizing area between adjacent electrodes to detect the temperature of the titanium-copper composite strip within the energizing area between adjacent electrodes. Based on the temperature detection result, the current input of the adjustable current power supply is adjusted to control the energizing temperature between 500 and 900 °C, with an effective energizing time of 5 to 15 seconds. The energizing process is carried out under a protective atmosphere, vacuum environment, or inert gas protection.

7. A titanium-copper composite strip prepared by a multi-pass rolling composite method according to any one of claims 1 to 6.

8. A multi-pass rolling composite device for titanium-copper composite strips, characterized in that, The system includes a titanium strip uncoiling mechanism, a first roll group, a second roll group, a third roll group, and a winding mechanism arranged sequentially along the production line; a copper strip uncoiling mechanism is arranged below the titanium strip uncoiling mechanism; guide mechanisms are arranged between the titanium strip uncoiling mechanism and the first roll group, and between the copper strip uncoiling mechanism and the second roll group; the first roll group includes a first lower surface morphology roll located below the titanium strip and a first upper polishing roll located above the titanium strip; the second roll group includes a second upper surface morphology roll and a second lower polishing roll; and the third roll group includes two flat rolls.

9. The multi-pass rolling composite apparatus for titanium-copper composite strip according to claim 8, characterized in that, It also includes an online energizing treatment device, which is set between the third roll group and the winding mechanism. The online energizing treatment device includes at least two electrodes and a temperature detection device that are spaced apart along the strip running direction. The electrodes are in conductive contact with the titanium-copper composite strip and are connected to an adjustable current power supply. The temperature detection device is set in the energized area between adjacent electrodes and is used to detect the temperature of the titanium-copper composite strip in the energized area.

10. A multi-pass rolling composite apparatus for titanium-copper composite strips according to claim 9, characterized in that, Surface morphology detection sensors are respectively installed between the first roll group and the second roll group, above and below the single-sided morphology titanium strip. The surface morphology detection sensor located above is used to detect the surface state of the smooth surface on the upper side of the titanium strip, and the surface morphology detection sensor located below is used to detect the surface roughness or contour parameters of the morphology surface on the lower side of the titanium strip. When the test results meet the preset range, the strip continues to run; when the test results of the lower surface morphology do not meet the preset range, the feeding stops and the first lower surface morphology roller is adjusted or replaced; when the test results of the upper surface finishing do not meet the preset range, the feeding stops and the first upper polishing roller is inspected, adjusted or replaced.